Process Optimization of Advertising Articles Using an Integrated Strategy of Production and Environmental Care - Espejo Viñán, Hernán Fabricio (2021)
Global pollution has brought together several countries over time in order to reduce global warming by about 1.5 °C, as the productive sector is one of the main causes, It is suggested to use the model proposed by UNEP and UNIDO for Cleaner Production (C+P), aiming at reducing raw material consumption and waste reduction; analysis on production processes is started to obtain data on the use and waste generation, using descriptive statistics and Pareto analysis in the 2019 processes, the main causes are identified through the 6 Ms of Ishikawa, so it is concluded that 2 raw materials are responsible for more than 88% of waste, thereafter, it is identified that the highest percentage of waste is below the central limit through the use of C+P and statistical process control, which is expected to reduce waste and environmental impact by 18% and increase productivity by 22%.